A comparative study of morbidity pattern among rural and urban postmenopausal women of Allahabad, Uttar Pradesh, India - Goyal, Ankita; Mishra, Neha; Dwivedi, Shraddha (International Journal of Research in Medical Sciences, 2017)
Background: Menopause is an inevitable reproductive phase during midlife when various physical and mental changes may impair the quality of life of women. Middle-aged women may experience a wide range of physical and psychological symptoms. Decrease in the production of estrogen leads to the premenopausal symptoms of hot flushes, insomnia and mood changes, as well as post-menopausal osteoporosis and vaginal atrophy, leading to decrease in quality of life. Methods: Community based cross-sectional study. Door to door survey was conducted among women who had attained menopause for more than 1 year, in rural and urban area of Allahabad. Multistage random sampling was done. 400 postmenopausal women, 200 each from rural and urban area were selected. A pre-tested structured questionnaire was used for data collection. Results: Majority were in the age group of 50-60 years followed by 60-70 years. Majority of women were having a parity of 3. Vasomotor symptoms were experienced by 34.5% and 39.5% rural and urban women respectively. Out of total post-menopausal women who reported genitourinary complaints, the most commonly reported complaint was stress incontinence i.e. 10.5% and 8.5% respectively in rural and urban communities followed by increased urinary frequency i.e. 9% and 7.5% respectively in rural and urban areas. Vaginal dryness was reported by 2.5% of rural women and 6% of urban women. Vaginal discharge was reported by 7% of rural and 4% of urban women. Uterine Prolapse was reported by 6% of rural women and 3.5% of urban women. Conclusions: The study shows that postmenopausal women in India suffer from various vasomotor, physical as well as psychiatric problems related to menopausal hormonal changes with varied frequencies. There is a need to address their problem and establish health care centers for them. Postmenopausal women should be sensitized for availing the health facilities for their health problems by information education and communication (IEC) and behaviour change communication (BCC). Family support should be ensured by creating awareness in community. Awareness regarding menopause and problems among women related to it need to be improved. Health workers, ASHA, Aanganwadi workers can help women to understand about the menopausal symptoms, if they are given adequate training.